1974
DOI: 10.1136/oem.31.2.113
|View full text |Cite
|
Sign up to set email alerts
|

Renal ultrastructure, renal function, and parameters of lead toxicity in workers with different periods of lead exposure

Abstract: , larion H. (1974). British Journal of Industrial Medicine, 31, 113-127. Renal ultrastructure, renal function, and parameters of lead toxicity in workers with different periods of lead exposure. Renal biopsies were obtained from five men with heavy occupational exposure to lead and compared with studies of their renal function and parameters of lead toxicity. Two men had lead exposure of less than one year while three men had been exposed for from four to more than 30 years. In addition, renal function studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
46
0
4

Year Published

1981
1981
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(50 citation statements)
references
References 30 publications
0
46
0
4
Order By: Relevance
“…Two studies reported only on young children (Ͻ10 years), 25,37 two studies were case reports, 45,48 one 66 recruited less than 50 persons, in one 54 owing to missing information the analysis was performed in less than 50 subjects, five estimated exposure from other measurements than the blood lead concentration, 30,77,78,81,88 and 11 did not provide enough information to compute the association size. 17,19,22,26,27,36,39,62,63,67,86 …”
Section: Selection Of Studiesmentioning
confidence: 99%
“…Two studies reported only on young children (Ͻ10 years), 25,37 two studies were case reports, 45,48 one 66 recruited less than 50 persons, in one 54 owing to missing information the analysis was performed in less than 50 subjects, five estimated exposure from other measurements than the blood lead concentration, 30,77,78,81,88 and 11 did not provide enough information to compute the association size. 17,19,22,26,27,36,39,62,63,67,86 …”
Section: Selection Of Studiesmentioning
confidence: 99%
“…Renal effects in man have been described in clinical reports (21,24,35), by studies of renal function (14,23,33,38,47), and by epidemiologic studies. For example, Lane (19,20) Because, as Lane (19) pointed out, animals exposed to lead have shown both tubular and vascular changes in the kidneys, it is of interest that in our study there were excess deaths in both the chronic nephritis and the renal vascular disease categories.…”
Section: Chronic Renal Diseasementioning
confidence: 99%
“…In animal experiments, Goyer et al11,12) described intranuclear inclusion bodies induced by lead. Cramer et al 13) reported the pathological findings of intranuclear inclusion bodies in lead exposed workers.…”
mentioning
confidence: 99%